Simulation of single and dual layered rapid pressure swing adsorption - Lai, Yin Ling (2013)
Rapid Pressure Swing Adsorption (RPSA) is a cyclic process where the bed is repeatedly being subjected to rapid adsorption and desorption. The process is inherently dynamic and exhibits cyclic steady state (CSS) after sufficient number of cycles. In this thesis, two novel methods of successive substitution (MSS) accelerators are developed. The novel MSS accelerators possess three important features (i) speeding the convergence to CSS, (ii) determining the CSS unambiguously, and (iii) preserving the process variable profiles at CSS. The MSS accelerators incorporate a hybrid algorithm which combines the MSS and (i) Aitken and (ii) Muller updating scheme, and a stopping criterion. Both hybrid algorithms are tested on a cyclic process, controlled-cycle stirred tank reactor (CCSTR) described by a non-linear algebraic equation. The Muller hybrid algorithm is found to achieve CSS faster and is then adopted for the simulation of RPSA for air separation. It is found that the Muller hybrid algorithm is able to reduce the number of cycles required to reach CSS by 50%. The process variable profiles at CSS obtained from the algorithm are also found to be in excellent agreement with the MSS simulation. A dual layered RPSA model is then developed. Verification of the applied numerical methods and computer programs are carried out successfully that the simulated results agree well with the analytical solutions and experimental data. The optimum pressurization to depressurization time ratio for the dual layered RPSA is first determined. Effects of particle sizes (300:100 μm to 300:500 μm), types of adsorbents (Zeolites 5A and AgLiX), and having non-adsorptive particles in oxygen product purity and recovery are then studied. Depending on the ratio of the length of the first layer to the length of the bed, , the dual layered RPSA is found to improve the oxygen product purity by 16% - 20% for particle size of 300:100 μm. It is also found that the oxygen product purity increases by almost 20% when the first layer is packed with Zeolite AgLiX and Zeolite 5A in the second layer. Higher pressure drop across the bed is induced when particles of smaller pressure drop are used in the first layer and particles of larger pressure drop are used in the second layer, hence leading to better separation. Nevertheless, the oxygen product recovery is found to be insensitive to these new configurations. The dual layered RPSA packed with non-adsorptive particles is found to have reduced the oxygen product purity. Hence, replacing the adsorbent at the product end will not help in reducing the amount of adsorbent needed for the operation.